STUDI ETNOBOTANI JENIS-JENIS TUMBUHAN OBAT PADA MASYARAKAT BADUY BANTEN SELATAN - Johan Iskandar (BIOTIKA Jurnal Ilmiah Biologi, 2005)
Ethnobotanical research on use of various plants for medical purposes was undertaken in Baduy area in 1994/1995 and 2004. The semi-structure interviewing with key informants and the field inventory of various medicinal plants in several land-use types of the Baduy were applied. The result of study shows that the Baduy community has intensively used various medicinal plants to cure some illnesses. However, some modern medicines have also selectively adopted by some Baduy people, particularly Outer Baduy. This is caused by intensive penetrating market economy and providing modern medicines by tourists who have come to Baduy village. The herbal medicines of the Baduy community have been mainly collected from several indigenous land use types, particularly dukuh lembur, huma, reuma and leuweung kolot.